Changes in post-event processing and metacognitions during cognitive behavioral group therapy for social phobia - McEvoy, Peter; Mahoney, A.; Perini, S.; Kingsep, P. (Pergamon, 2009)
This study examined changes in post-event processing (PEP),metacognitions, and symptoms of socialanxiety and depression following cognitive behavioral group therapy for social phobia (N = 61). Socialanxiety, depression symptomsand PEP all significantly reduced following treatment. Reductions in PEPwere associated with reductions in symptoms of social anxiety, but not depression. Metacognitionswere also less strongly endorsed following treatment, with the exception of positive metacognitions.Interestingly, however, changes in metacognitions were generally associated with reductions in depression and not social anxiety. Theoretical and clinical implications as well as future researchdirections are discussed.